The impact of cytokines, hormones, and trace elements on Alzheimer’s disease progression: A case-control study - Farag, A. H. (Regulatory Mechanisms in Biosystems, 2025)
Alzheimer’s disease is a progressive neurodegenerative disorder characterized by cognitive decline, memory impairment, and behavioral disturbances. The aims of the study is evaluate the impact of cytokines, hormones, and trace elements on the progression of Alzheimer’s disease. A case control study involved 150 Alzheimer’s disease patients (75 males, 75 females) and 75 controls (37 males, 38 females) aged 64–75 years. Diagnosis was confirmed by neurologists, with ethical approval and i n formed consent obtained. Blood samples were collected, and serum was analyzed for IL-6, TNF-α, IL- 10 , amyloid beta protein , tau protein , homocysteine , cortisol , estradiol , testosterone , zinc , copper , and selenium using ELISA, Cobas, and spectrophotom e try. This study found significant differences between Alzheimer’s disease patients and controls. Alzheimer’s disease patients showed increased levels of cytokines IL-6 and TNF-α, and decreased IL-10. Hormonal assessments revealed higher cortisol and lower estradiol and testosterone. Trace elements like zinc and selenium were lower, while copper was higher. Key biomarkers (amyloid beta, tau protein, homocysteine) were also elevated in AD patients. This study highlights the role of cytokines, ho r mones, and trace elements in Alzheimer’s disease development. Increased levels of cytokines, cortisol, and trace elements suggest inflammation and metabolic imbalance in Alzheimer’s disease. Monitoring these biomarkers could aid in disease management and therapeutic intervention.